2013
DOI: 10.1007/s00248-013-0219-y
|View full text |Cite
|
Sign up to set email alerts
|

Variations in Diversity and Richness of Gut Bacterial Communities of Termites (Reticulitermes flavipes) Fed with Grassy and Woody Plant Substrates

Abstract: Diets shape the animal gut microbiota, although the relationships between diets and the structure of the gut microbial community are not yet well understood. The gut bacterial communities of Reticulitermes flavipes termites fed on four individual plant biomasses with different degrees of recalcitrance to biodegradation were investigated by 16S rRNA pyrosequencing analysis. The termite gut bacterial communities could be differentiated between grassy and woody diets, and among grassy diets (corn stover vs. sorgh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
46
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(55 citation statements)
references
References 28 publications
6
46
3
Order By: Relevance
“…Much evidence suggests that the bacterial diversity of the gut microbiota is essential for maintaining gut homeostasis (Boucias et al., 2013; Hu, Lukasik, Moreau, & Russell, 2014). In the gut of Reticulitermes flavipes termites, a diet of corn stover reduced the bacterial richness and diversity, compared with sorghum and two other woody diets (Huang et al., 2013). However, in the gut of M. shangchengensis , the bacterial richness and diversity both increased after feeding on corn stalks and filter paper, compared to wood.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Much evidence suggests that the bacterial diversity of the gut microbiota is essential for maintaining gut homeostasis (Boucias et al., 2013; Hu, Lukasik, Moreau, & Russell, 2014). In the gut of Reticulitermes flavipes termites, a diet of corn stover reduced the bacterial richness and diversity, compared with sorghum and two other woody diets (Huang et al., 2013). However, in the gut of M. shangchengensis , the bacterial richness and diversity both increased after feeding on corn stalks and filter paper, compared to wood.…”
Section: Discussionmentioning
confidence: 99%
“…Firstly , the diet has significant effects on the gut microbiome of both lower and higher termites (Boucias et al., 2013; Huang, Bakker, Judd, Reardon, & Vivanco, 2013). For example, the gut bacterial community of the lower termite Reticulitermes flavipe can be differentiated on the basis of grassy and woody diets as well as among different grassy diets (Huang et al., 2013). In the higher termite Nasutitermes takasagoensis , variations in the termite gut microbial community structures depend on the dietary composition (Miyata et al., 2007).…”
Section: Introductionmentioning
confidence: 99%
“…The great similarity of the gut microbiota within and among colonies of the same termite species (e.g., 44,92,95) suggests that proctodeal trophallaxis stabilizes the microbial community structure within a colony and ensures the faithful transfer of symbionts across generations, which should ultimately lead to cospeciation. However, cocladogenesis with the termite host has so far been firmly established only in the case of "Candidatus Azobacteroides pseudotrichonymphae," an endosymbiont of Pseudotrichonympha flagellates, and termites of the family Rhinotermitidae, which cospeciate with these flagellates, giving rise to a termite-specific clade of bacterial symbionts (76).…”
Section: Evidence For Cospeciationmentioning
confidence: 99%
“…Recent studies have indicated that different dietary habits shape the structure of microbiota in the termite gut (Boucias et al, 2013;Huang et al, 2013;Raychoudhury et al, 2013). Dietary manipulation induces measurable differences among gut bacterial communities, and the recalcitrance of plant substrates may be the major cause of this variation in the diversity and richness of gut bacterial communities (Boucias et al, 2013;Huang et al, 2013;Raychoudhury et al, 2013). However, influences on the abundance and diversity of the intestinal microbial of termite fed with different substrates containing various lignin and cellulose or hemicellulose remain unclear.…”
Section: Introductionmentioning
confidence: 99%
“…The diversity and complexity of the termite gut microbiota have been evaluated using molecular technology techniques based on 16S rRNA (Warnecke et al, 2007;Berlanga et al, 2011;Mathew et al, 2012). Recent studies have indicated that different dietary habits shape the structure of microbiota in the termite gut (Boucias et al, 2013;Huang et al, 2013;Raychoudhury et al, 2013). Dietary manipulation induces measurable differences among gut bacterial communities, and the recalcitrance of plant substrates may be the major cause of this variation in the diversity and richness of gut bacterial communities (Boucias et al, 2013;Huang et al, 2013;Raychoudhury et al, 2013).…”
Section: Introductionmentioning
confidence: 99%